On the generalized eigenfunctions system of the Sturm–Liouville problem - Pečiulytė, Sigita; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2008)
In this paperwe investigate eigenfunctions and generalized eigenfunctions system of the Sturm– Liouville problem with classical boundary condition on the left boundary and nonlocal boundary conditions of four types on the right boundary.